UPAYA PENINGKATAN KINERJA APARATUR SIPIL NEGARA PADA BIRO ORGANISASI SEKRETARIAT DAERAH PROVINSI SUMATERA SELATAN - Tiansah, Agus (PRAJA: Jurnal Ilmiah Pemerintahan, 2025)
State Civil Apparatus, hereinafter abbreviated as ASN according to Law of the Republic of Indonesia Number 5 of 2014 concerning State Civil Apparatus, is a profession for civil servants and government employees with work agreements who work in government agencies. The implementation of public services will be realized determined by various factors, including the professionalism of the apparatus, while to get a professional apparatus requires the quality of apparatus resources in accordance with the demands of the organization, this is important and essential because public services are services that are directly related to meeting the needs of the wider community and greatly affect the achievement of overall organizational goals. This study aims to analyze performance improvement efforts at the Bureau of Organization of the Regional Secretariat of South Sumatra Province. This research uses a descriptive method with a qualitative approach. The data collection techniques used in this research are interviews, observation, and documentation. There are performance indicators in efforts to improve performance in employees including indicators of Work Quality, Timeliness, Initiative, Ability, and Communication. The results of the research conducted show that performance improvement efforts are appropriate in improving employee performance. However, there are still shortcomings experienced by the State Civil Apparatus (ASN) in improving performance efforts.